Makna Kata τέλειος Dalam Injil Matius 5:48 Dan Implikasinya Bagi Orang Percaya - Fajar Gumelar; Christopher James Luthy; Robi Panggarra; Hanny Frederik (Institut Agama Kristen Negeri Toraja, 2021)
Abstract: Matthew 5:17-48 is part of Jesus' Sermon on the Mount, where it is the deepest reflection of God's law which contrasts sharply with the patterns and teachings of the scribes and Pharisees. This passage concludes with Jesus' mandate to His followers to be perfect as their Father in heaven is perfect (5:48). The word perfect in this text is translated from the Greek word τέλειος which can actually be translated as perfect, complete or mature. The difference in interpretation of the meaning of the word τέλειος has led to several different thoughts and doctrines. In Matthew 5:48's research, the author uses general hermeneutic principles to find the meaning or meaning conveyed by the author to the first reader. This research used the critical historical interpretation method. In addition, the author also uses library research methods, by reading books, journals and investigating books related to the discussion of this scientific work. Based on the description of this scientific work, the authors draw the following conclusions: first, the meaning of the word τέλειος in Matthew 5:48 does not refer to a sinless perfect state, but rather to the meaning of completeness. Second, the example of life for believers is God himself, not others. Third, the command to be perfect like God is not an impossible thing for God's people to do. Fourth, completeness like God can only be experienced if humans have an intimate relationship with God. Fifth, Jesus calls His people to be complete in fellowship. Abstrak: Matius 5:17-48 merupakan bagian dari khotbah Yesus di bukit, dimana isinya merupakan refleksi terdalam terhadap hukum Allah yang sangat kontras dengan pola dan ajaran ahli-ahli Taurat dan orang-orang Farisi. Perikop ini diakhiri dengan amanat Yesus kepada para pengikut-Nya untuk menjadi sempurna sebagaimana Bapa di surga adalah sempurna (5:48). Kata sempurna dalam teks ini diterjemahkan dari kata Yunani τέλειος yang sebenarnya bisa diterjemahkan sebagai sempurna, lengkap atau dewasa. Perbedaan tafsir akan makna kata τέλειος ini kemudian memunculkan beberapa pemikiran dan doktrin yang berbeda-beda. Dalam penelitian Matius 5:48 ini penulis menggunakan prinsip-prinsip umum hermeneutik guna mencari makna atau maksud yang disampaikan penulis kepada pembaca pertama. Metode tafsir yang digunakan adalah metode tafsir historis kritis. Selain itu penulis juga menggunakan metode penelitian kepustakaan atau library research, dengan membaca buku-buku, jurnal-jurnal dan menyelidiki kitab yang berkaitan dengan bahasan karya ilmiah ini. Berdasarkan hasil uraian dari karya ilmiah ini, penulis menarik kesimpulan sebagai berikut: pertama, makna kata τέλειος dalam Matius 5:48 tidak menunjuk pada keadaan sempurna yang tanpa dosa, melainkan pada arti kelengkapan. Kedua, keteladanan hidup bagi orang percaya adalah Allah sendiri, bukan orang lain. Ketiga, perintah untuk menjadi sempurna seperti Allah bukanlah suatu hal yang mustahil untuk dilakukan umat Allah. Keempat, kelengkapan seperti Allah hanya dapat dialami jika manusia memiliki hubungan yang intim dengan Allah. Kelima, Yesus memanggil umat-Nya untuk menjadi lengkap di dalam persekutuan.